Perencanaan Instalasi Pengolahan Air Limbah Desa Siulak Gedang Kecamatan Siulak Kabupaten Kerinci - Fajar Arsyadani; Monik Kasman; Ira Galih Prabasari (Universitas Batanghari Jambi, 2021)
Siulak Gedang, a village lies on Siulak District, Kabupaten Kerinci which has old common treatment system for its domestic wastewater system. Black water is treated in impermeable septic tank so that the wastewater directly seeps into the ground is discharged into public drains. Meanwhile, grey water is channeled directly into the public drainage. Thus, domestic wastewater treatment is needed for Siulak Gedang Village to avoid water pollution due to the direct discharge of wastewater. The design for domestic wastewater system is divided into 2 parts of wastewater treatment plant (Instalasi Pengolahan Air Limbah = IPAL) that operates simultaneously using anaerobic baffled reactor (ABR) which combined with constructed wetland. Based on the calculation, the peak discharge of population services is 2198,4 m3/day. The IPAL consists of a grease trap as a separator for oil and grease, a collection tank, a distribution tank, an ABR tank as the main processing unit for wastewater and further processing with a constructed wetland in sanitary pool.